213k views
5 votes
What is the radius of the circle defined by x2 + 2x + y2 + 6y − 39 = 0?

49
9
7
81

2 Answers

1 vote

Answer:

7 units

Explanation:

(h,k) = (-2/2, -6/2) = (-1,-3)

(-1)² + (-3)² - (-39) = r²

49 = r²

r = 7

User Wbruntra
by
5.7k points
4 votes

radius = 7

the equation of a circle in standard form is

(x-a)² + (y-b)² = r²

where (a, b) are the coordinates of the centre and r is the radius

To obtain this form ' complete the square ' on both the x and y terms

x² + 2(1)x + 1 + y² + 2(3)y + 9 = 39 + 1 + 9

(x+1)² + (y+3)² = 49 ← in standard form

with centre (1, 3) and r = √49 = 7



User Daniel Cukier
by
5.8k points